Kanun-u Esasi’de padişahın statüsü - Boyalık, Ramazan (My University, 2007)
Kanun-u Esâsî’de Padişahın Statüsü Osmanlı padişahlarının eski Türklerden gelen anlayışlarla İslamî anlayışın bir sentezi olan statüsü, geçirdiği tarihî değişim ve gelişimlerle beraber Kanun-ı Esâsî’ye kadar gelmiş ve Kanun-ı Esâsî’yle bu teorik ve fiili durum, bazı kısıtlamalarla birlikte yazılı anayasa kaidesi haline getirilmiştir. Bununla beraber Kanun-ı Esâsî’de, meşruti ya da parlamenter monarşilerde krala verilmeyen birçok yetki padişaha verilmiştir. Padişahın gerek Heyeti Vükelâ’nın kuruluş ve işleyişi gerekse yasamayla ilgili önemli yetkileri vardır. Heyeti Vükelâ üyelerinin atanması/ azli, Heyeti Vükelâ’nın işleyişi, Meclislerin çalışma takvimleri ve kanun yapma süreci ile ilgili yetkileri, meclislerden geçen kanunları “mutlak veto yetkisi”, Âyân Meclisinin bütün üyelerinin ve meclis başkanlarının padişah tarafından atanması, yasama ve yürütme alanlarında padişahın etkisinin ve vesayetinin devam ettiğini göstermektedir. 7 ve 35. maddelerde seçim dışında herhangi bir kısıtlama getirilmeksizin padişaha verilen Mebusân Meclisini fesih yetkileri, yasama ile yürütme arasındaki dengeyi yürütme lehine bozmuştur. Ancak tüm kısıtlamalara rağmen, Kanun-ı Esâsî ile birlikte kurulan meclisler, yasama yetkisine sahiptirler. Artık padişah, meclislerden geçmeyen bir kanun ihdas etme yetkisine sahip değildir. Padişahın yargı yetkisi ise bağımsız mahkemelere devredilmiştir. Kanun-ı Esâsî’de yapılan 1909 değişiklikleriyle, parlamenter hükümet tarzı kabul edilmiştir. Padişah, yasama ve yürütmeyle ilgili birçok yetkilerini yitirmiş, hükümetin sadece parlamento önünde sorumluluğu esası benimsenmiştir. Meclisin icabında güvensizlik oyuyla hükümeti düşürebilmesini sağlayacak müeyyideler getirilmiştir. Ayrıca meclisin feshi şartları da ağırlaştırılarak parlamentonun konumu güçlendirilmiştir. Yapılan bu değişikliklerle devletin monarşik yapısı korunmakla birlikte, padişahın statüsünde önemli kısıtlamalar gerçekleştirilmiştir. Böylece Avrupa’nın taçlı monarşilerinden aşağı olmayan “gerçek anlamda meşruti bir monarşi” düzenine geçilmiştir.

The Status of The Sultan in Kanun-u Esasi The status of the Ottoman sultans has born from the synthesis of earlier Turkish traditions and Islamic understanding. This status has continued till Kanun-i Esâsî (the Ottoman Basic Law) wit some changes and transformations. Kanun-i Esâsî has transformed this theoretical status into a written constitutional principle with some restrictions. Beyond that, there have been many authorities for the Sultan in Kanun-i Esâsî which had not been for the kings in constitutional or parliamentary monarchies. Accordingly, the Sultan legally had the authority on the establishment and the execution of Heyet-i Vukela (the Council of Ministers). There are some remarkable examples for the authority of the Sultan on Heyet-i Vukelâ such as the assignment and dismissal of the members of Heyet-i Vukelâ, its execution, the right to intervention to the calendar of the assemblies and their jurisdiction processes, his absolute right to veto, assignment of all the members of the Senate and the presidents of the assemblies by the Sultan. The authority of Sultan to avoid of the Ottoman Assembly of Deputies without any restrictions but the elections, by the articles numbered 7 and 35, has changed the balance between the jurisdiction and the execution in favor of the execution. Despite all the restrictions, the assemblies established by Kanun-i Esâsî had the authority of jurisdiction. From Kanun-i Esâsî on, the Sultan had no authority to introduce new laws that had not passed through the assembly. The authority of the Sultan to judge has also been ceded to the impartial courts. By the changes on Kanun-i Esâsî in 1909, parliamentary system was accepted. Moreover, the Sultan lost most of his authorities on jurisdiction and judgment. The government has been responsible only before the parliament. There have been some new sanctions on the government to be brought down by the parliament. Additionally, the status of the parliament has been strengthened by making difficult of annihilating the assembly. By these changes, the status of the Sultan has been diminished remarkably while protecting the monarchic structure of the state. Therefore, it has been possible to have a “real constitutional monarchy” which was not less valuable than that of the European crowned monarchies.
Keywords: Hukuk_Kanun-u Esasi; Kamu Hukuku_Osmanlı İmaparatorluğu